A VERTICALIZAÇÃO LITORÂNEA EM VILA VELHA/ES: UM ESTUDO DE CASO. - Holz, Schirley (2020)
The study addresses coastal verticalization on the shore of Vila Velha, a county that integrates the Great Metropolitan Region of Vitória (RMGV), specifically in the first blocks from the sea located in the neighborhoods of Praia da Costa, Itapuã and Prai